If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7t + 16 = 9 Reorder the terms: 16 + 7t = 9 Solving 16 + 7t = 9 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + 7t = 9 + -16 Combine like terms: 16 + -16 = 0 0 + 7t = 9 + -16 7t = 9 + -16 Combine like terms: 9 + -16 = -7 7t = -7 Divide each side by '7'. t = -1 Simplifying t = -1
| x=8y/3 | | -5x-23=-3 | | -2(6x-4)=4(3x+1)+4 | | 2a+3b=18 | | -2x+5x^7-4x+7x^7+4= | | 5x-9=-23 | | Y^11*y^0= | | x+3+5=11 | | (4/7+1/4)/(4/7-1/4) | | 2x^2-25y^2=0 | | 2x/56 | | (-4s^2+5s+2)-(6s^2+2)= | | 35x=-135 | | 3x+3(-3x+11)=-3 | | 4g-2+g+6-3g= | | 4x+3-2(x-5)=4-x | | -30=5/7 | | -7x+9y=-63 | | 2x*2-25y*2=0 | | 288=6x^2+30x | | 3/x+2/5x=0 | | 3/x+2/5=0 | | 108=x^2+6x | | 4x=1x+18 | | 5x+4+8x=30 | | t=c-q/q | | 15x+8-14x-15=3 | | 10x^2-13=0 | | 10x^3-13=0 | | 6(9y-3)-(7y+8)= | | -m^2-17m=0 | | 0.1r=4 |